ANCA-associated glomerulonephritis and lupus nephritis following COVID-19 vaccination: a case report and literature review - Campos, Marcos Adriano Garcia; Valois, Tiago de Oliveira; Magalhães, Luís Eduardo; Vasques, Lucas Fernandes; de Medeiros, Rafael Goulart; Costa, Denise Maria do Nascimento; Salgado Filho, Natalino; Nogueira, Raquel Moraes da Rocha; Neves, Precil Diego Miranda de Menezes; Silva, Gyl Eanes Barros (Frontiers in Immunology, 2024)
With the coverage of COVID-19 vaccination, it has been possible to observe the potential side effects of SARS-CoV-2 vaccines, with the most common ones being fever, myalgia, headache, and fatigue. However, an association has been observed between new and recurrent kidney injuries, mainly glomerulonephritis and lupus nephritis associated with ANCA, with the Pfizer-BioNTech, Moderna, Sinovac, and AstraZeneca vaccines, although the relationship between them is not clear. We report a case of ANCA-related vasculitis and lupus glomerulonephritis after the second dose of the AstraZeneca vaccine. The elderly patient presented significant worsening of kidney function after immunosuppression and complications after a new onset COVID-19 infection that led to death. We provide a literature review about kidney damage related to ANCA vasculitis after COVID-19 vaccine, aiming for a better understanding of the pathophysiological mechanism of kidney injury, its presentation, and treatment.